1995
DOI: 10.2307/3284031
|View full text |Cite
|
Sign up to set email alerts
|

Host Grooming and the Transmission Strategy of Heligmosomoides polygyrus

Abstract: Grooming behavior may play a part in the transmission of the gastrointestinal nematode, Heligomosomoides polygyrus in the mouse host. After infective larvae are placed on individually housed mice, significantly higher numbers of adult worms were recovered from the small intestine of mice that were allowed to self-groom when compared to infection levels in mice that had been fitted with Elizabethan collars to prevent self-grooming. Larvae placed on a single mouse housed with 3 other untreated mice resulted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 35 publications
4
48
1
Order By: Relevance
“…However, empirical evidence shows that gastrointestinal parasites, which usually have indirect transmission pathways, can also be transmitted through social interactions (e.g. during grooming, when infectious stages are ingested by the grooming actor from the fur of the grooming recipient [9,11]). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, empirical evidence shows that gastrointestinal parasites, which usually have indirect transmission pathways, can also be transmitted through social interactions (e.g. during grooming, when infectious stages are ingested by the grooming actor from the fur of the grooming recipient [9,11]). …”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence suggests that all of these parasites can be transmitted through interactions involving physical contact. For example, grooming has been shown to facilitate the transmission of nematode species in mice (Mus musculus) [11] and Japanese macaques (Macaca fuscata yakui) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Species description and monitoring H. polygyrus inhabits the small intestine of yellownecked mice and has a direct life cycle with infection occurring after the ingestion of third-stage larvae, either with contaminated food or through grooming (Slater and Keymer, 1986 ;Hernandez and Sukhdeo, 1995). Adult males, as opposed to females, were responsible for the majority of the nematode transmission (Ferrari et al 2004).…”
Section: A T E R I a L S A N D M E T H O D Smentioning
confidence: 99%
“…However, additional pieces were contributed to the story right through to the 1990s. The pre-parasitic stages were studied by Fahmy (1956), but evidence for the principal route of transmission in the wild was provided almost 40 years later : Hernandez and Sukhdeo (1995) showed that infective larvae are acquired from host hair during grooming activities (Hernandez and Sukhdeo, 1995). These exsheath in the stomach and first invade the gastric mucosa, but then move to the small intestine where by the third day they have localized in the intestinal walls (Liu, 1965 ;Sukhdeo, O'Grady and Hsu, 1984).…”
Section: H E L I G M O S O M O I D E S B a K E R I O R H P O L Y G Ymentioning
confidence: 99%